2001
DOI: 10.1200/jco.2001.19.21.4097
|View full text |Cite
|
Sign up to set email alerts
|

Oral Capecitabine Compared With Intravenous Fluorouracil Plus Leucovorin in Patients With Metastatic Colorectal Cancer: Results of a Large Phase III Study

Abstract: Oral capecitabine achieved an at least equivalent efficacy compared with IV 5-FU/LV. Capecitabine demonstrated clinically meaningful safety advantages and the convenience of an oral agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
449
6
13

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 941 publications
(499 citation statements)
references
References 32 publications
16
449
6
13
Order By: Relevance
“…These trials demonstrated that capecitabine showed increasing efficacy in terms of response rate, equivalent time to progression and survival, and had a superior safety profile. 4,5,7 It is noteworthy that response rates were consistently higher for capecitabine than for 5-FU/LV in subgroups that included patients with liver metastasis (25% vs. 17%, respectively) and patients with lung metastasis (30% vs. 8%, respectively). 4 In our study, we found a strong anti-metastatic efficacy of capecitabine in the HT-29 cell rectal xenograft model wherein capecitabine showed low susceptibility in the xenograft itself.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These trials demonstrated that capecitabine showed increasing efficacy in terms of response rate, equivalent time to progression and survival, and had a superior safety profile. 4,5,7 It is noteworthy that response rates were consistently higher for capecitabine than for 5-FU/LV in subgroups that included patients with liver metastasis (25% vs. 17%, respectively) and patients with lung metastasis (30% vs. 8%, respectively). 4 In our study, we found a strong anti-metastatic efficacy of capecitabine in the HT-29 cell rectal xenograft model wherein capecitabine showed low susceptibility in the xenograft itself.…”
Section: Discussionmentioning
confidence: 97%
“…4 -6 Randomized clinical trials that compared capecitabine with parenteral 5-FU/leucovorin against metastatic colorectal cancer demonstrated that capecitabine provides at least equivalence, a favorable benefit-risk ratio and greater patient preference making it an acceptable replacement for 5-FU/leucovorin. 4,5,7 Our interest focused on the possibility of capecitabine usage in the prevention of metastasis. Neoadjuvant or adjuvant chemotherapy to inhibit spontaneous metastasis or suppress occult micrometastasis may reduce the incidence of postoperative distant metastasis and improve survival.…”
mentioning
confidence: 99%
“…Since the efficacy and favourable safety profile of capecitabine have been clearly demonstrated in recent large phase III studies comparing capecitabine with intravenous 5-FU plus leucovorin for metastatic colorectal cancer (Hoff et al, 2001;Van Cutsem et al, 2001), capecitabine has been widely used in the treatment of breast cancer, stomach cancer, and other solid tumours (Blum et al, 1999;Kim et al, 2002Kim et al, , 2003. Capecitabine also offers a number of potential advantages as a chemoradiosensitiser in concurrent chemoradiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In a preclinical study, capecitabine given orally resulted in consistently higher tissue-to-plasma 5-FU concentration ratios than 5-FU administered intravenously . In addition, capecitabine has also exhibited antitumour activity when given as a monotherapy or in combination with cisplatin in patients with various solid tumours as well as in advanced HNSCC (Blum et al, 1999;Van Cutsem et al, 2001;Kim et al, 2002;Pivot et al, 2003;Park et al, 2004).…”
mentioning
confidence: 99%
“…Oral fluorinated pyrimidines may mimic continuous regimens without its technical inconvenience and deterring patients' quality of life. In patients with advanced colorectal cancer, the efficacy of UFT (typical and most prescribed O-FP) plus oral LV (Carmichael et al, 2002;Douillard et al, 2002) or of capecitabine alone (Hoff et al, 2001;Van Cutsem et al, 2001) seems comparable in terms of the efficacy with significantly less significant severe haematologic toxicities and/or stomatitis. The risk of severe hand-foot syndrome is lower in UFT than with capecitabine, but the risk of severe diarrhoea and other gastrointestinal symptoms is higher in UFT and in UFT/oral LV treatment for Western patients.…”
Section: Meta-analysis Of Uft For Rectal Cancer J Sakamoto Et Almentioning
confidence: 99%